2015
DOI: 10.5194/bg-12-4185-2015
|View full text |Cite
|
Sign up to set email alerts
|

Response of key stress-related genes of the seagrass <i>Posidonia oceanica</i> in the vicinity of submarine volcanic vents

Abstract: Abstract. Submarine volcanic vents are being used as natural laboratories to assess the effects of increased ocean acidity and carbon dioxide (CO 2 ) concentration on marine organisms and communities. However, in the vicinity of volcanic vents other factors in addition to CO 2 , which is the main gaseous component of the emissions, may directly or indirectly confound the biota responses to high CO 2 . Here we used for the first time the expression of antioxidant and stress-related genes of the seagrass Posidon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 74 publications
1
33
0
Order By: Relevance
“…Expression level analyses were performed for specific genes of interest (GOIs) (See Table 3 and Supplementary Table S1 list selected genes of interest, their functions and primer information): the glutathione related enzymes glutathione synthase (GSH-S), glutathione peroxidase (GPX), glutathione reductase (GR) and glutathione S-transferase (GST), the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), luminal binding protein (LBP) and Peroxiredoxin Q (PRXQ) 27 , 70 and three nitrate transportes (NRT1_6.3, NRT1_2.13 and NRT2). Glutathione-related and the other antioxidant enzymes were selected in order to study the cellular response to oxidative stress, while nitrate transporters were selected to investigate variations in nitrogen uptake upon nutrient-enrichment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression level analyses were performed for specific genes of interest (GOIs) (See Table 3 and Supplementary Table S1 list selected genes of interest, their functions and primer information): the glutathione related enzymes glutathione synthase (GSH-S), glutathione peroxidase (GPX), glutathione reductase (GR) and glutathione S-transferase (GST), the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), luminal binding protein (LBP) and Peroxiredoxin Q (PRXQ) 27 , 70 and three nitrate transportes (NRT1_6.3, NRT1_2.13 and NRT2). Glutathione-related and the other antioxidant enzymes were selected in order to study the cellular response to oxidative stress, while nitrate transporters were selected to investigate variations in nitrogen uptake upon nutrient-enrichment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Lauritano, et al . 27 compared the expression of genes involved in the response to stress between plants collected at low natural pH, near volcanic vents, and plants collected at normal pH conditions. These authors found increased expression of some antioxidant and stress-related genes in epiphyte-free leaves of P. oceanica close to vents, suggesting overall negative effects of increased CO 2 and low pH on plant physiology, possibly triggered by extensive leaf epiphyte loss 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, the differential regulation of proteins involved in the AsA-GsH cycle and flavonoid pathway indicates that SSL conditions triggered the plant antioxidant defense system, which improved the redox status and thus the SSL tolerance of Z. muelleri . Differential regulation of these antioxidant enzymes has been well documented as a defense response of seagrasses to light stress, heavy metal toxicity, and ocean acidification (Li et al, 2012; Dattolo et al, 2013; Lauritano et al, 2015). However, down-regulation of superoxide dismutase (SOD-Cu/Zn) and germin-like protein (that has both SOD and oxalate oxidase activity) suggests that this species is sensitive to high light stress.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular events precede population-level changes and could be useful biomarkers if they can be linked to specific physiological or ecological events (Macreadie et al, 2014b). Thus, seagrass researchers have recently taken advantage of the power of genomics and transcriptomics to address questions about the molecular mechanisms of ecological responses to environmental perturbations (Franssen et al, 2011, Franssen et al, 2014, Dattolo et al, 2014, Serra et al, 2012, Lauritano et al, 2015, Salo et al, 2015, Brakel et al, 2014. Following the recent publication of Zostera marina genome (Olsen et al, 2016), the seagrass community is now eagerly awaiting the progress that will be promoted by integrating molecular biology and gene expression into the spectrum of physiological and metabolic changes involved in the response of seagrass to environmental stress.…”
Section: Introductionmentioning
confidence: 99%